2016
DOI: 10.1007/s10577-016-9527-7
|View full text |Cite
|
Sign up to set email alerts
|

Karyotype diversity suggests that Laonastes aenigmamus (Laotian rock rat) (Rodentia, Diatomyidae) is a multi-specific genus

Abstract: Laonastes aenigmamus (Khanyou) is a recently described rodent species living in geographically separated limestone formations of the Khammuan Province in Lao PDR. Chromosomes of 21 specimens of L. aenigmamus were studied using chromosome banding as well as fluorescent in situ hybridization (FISH) techniques using human painting, telomere repeats, and 28S rDNA probes. Four different karyotypes were established. Study with human chromosome paints and FISH revealed that four large chromosomes were formed by multi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 23 publications
0
1
0
Order By: Relevance
“…These findings collectively indicate a prevalent occurrence of C-banding across species ( Kakampuy et al 2013 ). The BrdU -banding findings revealed that the BrdU -banding patterns of chromosomes 1–5 in both males and females was consistent with those reported by Richard et al (2016) , with the degree change in the BrdU -banding clearly observed in all of them. Additionally, the chromosomal BrdU -banding patterns for the three stages of the S-phase resembled those described by Schempp (1981), categorized as early, middle, and late.…”
Section: Discussionsupporting
confidence: 87%
“…These findings collectively indicate a prevalent occurrence of C-banding across species ( Kakampuy et al 2013 ). The BrdU -banding findings revealed that the BrdU -banding patterns of chromosomes 1–5 in both males and females was consistent with those reported by Richard et al (2016) , with the degree change in the BrdU -banding clearly observed in all of them. Additionally, the chromosomal BrdU -banding patterns for the three stages of the S-phase resembled those described by Schempp (1981), categorized as early, middle, and late.…”
Section: Discussionsupporting
confidence: 87%
“…Cell cultures, BrdU treatments, metaphase preparations, and chromosome banding were performed according to our standard protocols [Richard et al, 2016] except that BrdU treatments were extended from 4 to 18 h before harvesting. For co-cultures of G. gorilla (MNHN-TCCV-1074) and T. iliacus fibroblasts, the same number of cells from each species was grown for 6 h before synchronization by fluorodeoxyuridine.…”
Section: Methodsmentioning
confidence: 99%